Italian False Friends. - Ferguson, Ronnie (Toronto Italian studies., 1994)
Ronnie Ferguson has confronted the much-neglected problem of `false friends, ' or deceptive cognates, with a dictionary which makes it possible for the student of Italian to alert her- or himself to the pitfalls.